PENGARUH KOMPETENSI DAN SELF-EFFICACY TERHADAP KINERJA GURU DENGAN MEDIASI KOMITMEN ORGANISASI (Studi pada Guru PNS SD di UPT Disdikpora Kecamatan Gringsing-Batang) - Supriyadi, Supriyadi (Students Journal of Economic and Management, 2012)
The purpose of this study was to examine and analyze the effect of competence and self effficacy on teacher performance with the mediation of organizational commitment in UPT Gringsing Batang District Education Office. Populations that were subjected to experiments is the entire civil service teachers in UPT Gringsing Batang District Education Office. In this study population numbered 178 people as object. Sampling using proportions using Taro Yamane formula or Slovin. Using Slovin formula can be seen that the number of samples in this study were 124 respondents. Mechanical testing data used in this study include test validity with factor analysis, the Cronbach alpha reliability test, the classic assumption test normality test, F test model and test of determination (Adjusted R Square), hypothesis testing, and test the effect of mediation or intervening. The results of the analysis and discussion of the research shows that teacher competence, self-efficacy, organizational commitment and teacher performance, everything has a value of KMO is greater than 0.5 it indicates that the sample adequacy criteria have been met. Loading factor for variable 13 items declared invalid competence, self-efficacy of 11 are all valid, organizational commitment of 24 items 21 items revealed a number of valid and Performance teacher of 14 items all valid, because the value of loading factor greater than 0.4. Reliability test results can be seen for the four variables Cronbach alpha values were above 0.7 so that the four variables are declared reliable. The test results are known hypothesis that the variable does not affect the competence of organizational commitment, self-efficacy has positive and significant impact on organizational commitment, competence, self-efficacy and organizational commitment have a positive and significant effect on the teacher performance test mediation.The result known that organizational commitment can not mediate the effect of competence and self-efficacy on teacher performance in UPT Gringsing Batang District Education Office. The results of the analysis demonstrate that the ability of the model to describe corretly the relationship variable competence, self-efficacy and organizational commitment on teacher performance is equal to 46.2%, while the rest of 53.8% is explained by other variables outside the model. Keywords: competence, self-efficacy, organizational commitment and teacher performance. Keywords: competence, self-efficacy, organizational commitment and teacher performance.